Auditoría financiera: ganancias por valor razonable de las de inversiones inmobiliarias bajo NIIF. - Valarezo Guerrero, Benito Eduardo (My University, 2022)
The research was developed in the analysis of the application of the International Financial Reporting Standards (IFRS), in this case IFRS 13 is responsible for measuring the fair value of investment properties owned by an entity, given that, through In this process, it is possible to evidence the profit or loss that can be obtained through the revaluation of an asset. The objective is to examine the accounting treatment and recording of the increase or loss component in the value of the asset and the gain from measurement at fair value of the investment properties of the real estate company. The methodology applied for this work is of the documentary and descriptive type, the information was obtained from scientific journals, accounting books and documents related to investment properties, from which primary and secondary information was obtained for the solution to the case raised in the that the fair value measurement is applied, obtaining a gain from the measurement of the real estate investment, and in turn, a deferred tax liability is generated. The necessary procedures are specified to obtain the measurement at fair value of the real estate investments, being that, for the present case, applying the described processes, a profit of $24,000.00 was obtained for the investment property and a deferred tax of $6,000.00 for the same, which were recorded in an accounting manner to record the expertise carried out and in this way grant reasonableness and security to the financial information of the entity examined.
La investigación se desarrolló en el análisis de la aplicación de las Normas Internacionales de Información Financiera (NIIF), en este caso la NIIF 13 se encarga de medir el valor razonable sobre las propiedades de inversión que posee una entidad, dado que, a través de este proceso es posible evidenciar la ganancia o pérdida que se puede obtener mediante la revaluación de un activo. El objetivo es examinar el tratamiento contable y registro del componente incremento o de la pérdida del valor del activo y la ganancia por medición a valor razonable de las propiedades de inversión de la inmobiliaria. La metodología aplicada para este trabajo es del tipo documental y descriptiva, la información se la obtuvo de revistas científicas, libros contables y documentos relacionados a las propiedades de inversión, de la que se obtuvo información primaria y secundaria para la solución al caso planteado en la que se aplica la medición por valor razonable obteniendo una ganancia por medición de la inversión inmobiliaria, y a su vez se genera un pasivo por impuesto diferido. Se especifican los procedimientos necesarios para obtener la medición a valor razonable de las inversiones inmobiliarias siendo así que, para el presente caso aplicando los procesos descritos se obtuvo $24.000,00 de ganancia por la propiedad de inversión y un impuesto diferido de $6.000,00 por la misma, los cuales fueron registrados de manera contable para dejar constancia del peritaje realizado y de esta manera otorgar razonabilidad y seguridad a la información financiera de la entidad examinada.
Keywords: PROPIEDAD; GANANCIA; MEDICIÓN; VALOR RAZONABLE